Green hydrothermal synthesis of CeO2 NWs–reduced graphene oxide hybrid with enhanced photocatalytic activity. Issue 1 (19th February 2014) - Huang, K.; Lei, M.; Wang, Y.J.; Liang, C.; Ye, C.X.; Zhao, X.S.; Li, Y.F.; Zhang, R.; Fan, D.Y.; Wang, Y.G.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, CeO2 nanowires–reduced graphene oxide hybrids (CeO2 NWs–RGO) were synthesized by a green hydrothermal method using CeO2 NWs and graphene oxide (GO) as raw materials. During the process of reduction of GO, hydrothermal condition with supercritical water provides thermal and chemical factors to synthesize RGO. The photocatalytic experimental results show that the CeO2 NWs–RGO hybrids exhibit enhanced photocatalytic activity for degradation of Rhodamine B (RhB) under UV-light irradiation. It is found that the degree of photocatalytic activity enhancement strongly depends on the mass ratio of RGO in the hybrids, and the remarkable photocatalytic activity is 20 times that of pristine CeO2 NWs when the loading amount of RGO is 8.0 wt%. The enhancement of photocatalytic activity can be attributed to the excellently elevated absorption ability for the dye through π–π conjugation as well as the effective inhibition of the recombination of photogenerated electrons because of the electronic interaction between CeO2 NWs and RGO sheets.